UPGRADING TEACHERS’ PROFESSIONAL DEVELOPMENT THROUGH ACADEMIC WRITING AND LEARNING MEDIA WORKSHOPS: A COMMUNITY SERVICE - Wahyuningsih, Sri; Nikmah, Alfu (Proceedings of Annual Conference on Community Engagement, 2023)
Community service is a part of lecturers’ responsibility. In this matter, we conducted community service to teachers in Madrasa located in Colo, Kudus. Due to the lack of knowledge and competence among teachers in academic writing skills and learning media development, we provided workshops on academic writing skills and learning media through PowerPoint and YouTube content. This was done through socialization, planning, implementation, and evaluation of the program conducted in June to August 2022. In this sense, we provided the ways, stages, and tips for writing articles. Moreover, we provided training on designing teaching materials using PowerPoint and YouTube. By participating in these workshops, teachers in Madrasa are encouraged to improve their competence in writing articles by sharing their teaching experiences and research in the form of books or journals. Also, they obtain meaningful information and experience through designing learning media through PowerPoint and YouTube. The community service provides contributions to teachers, especially in establishing collaboration with lecturers to write articles to be published in a book chapter. Interestingly, the book chapter was published in 2023 entitled “Innovation in English Learning Media in the 5.0 society era”.